Performance analysis of Worlds-2022 - Kleshnev, V. (BioRow, 2022)
This Newsletter presents scientific analysis of race results from the recent World Rowing Championships in Racice, Czech Republic. It discloses essential information on the current trends in modern elite rowing, and comprehensively covers in a very concise format the following topics: